Factors Related to the Utilization of the Integrated Health Services Center for the Elderly - Sunik Cahyawati; Windarti Rumaolat; Nur Sayid Jalaludin Rumi; Wiwi Rumaolat (Jurnal Ners, 2020)
Introduction: The health service center for elderly is a public health center program for the elderly so they can be are ready to face old age independently and healthy. The objective of the research was to find out if there was a relationship between the use of health services centers for the elderly and attitudes, family support, the role of cadres, and access distance to health services for elderly people.Methods: The method used was quantitative with a cross-sectional design; the sample  contained 121 respondents, elderly people aged over 60 , the study time was 4 weeks. The instrument used was a questionnaire. The variables were elderly people’s attitudes, cadre roles, family support and the distance to the health service. The analysis was done using chi-square with a significant p-value (α <0,05).Results: The study obtained a significant relationship between the attitudes of the elderly p-value (0.001), family support p-value (0.00), the role of cadre p-value (0.00) and the use of the elderly health services center while the distance to the Integrated health center was not significantly related p-value (0.513).Conclusion: There is a relationship between the attitudes of the elderly, family support, the role of cadres to the use of elderly health services center while there is no relationship between the distance to access the health services center and the use of elderly.